Fighting (for) the margins: Trade union responses to the emergence of cross-border temporary agency work in the EU - Heinrich, Steffen [Verfasser]; Shire, Karen [Verfasser]; Mottweiler, Hannelore [Verfasser] (My University, 2020)
"Recent research suggests that trade unions in the European Union have become more receptive towards temporary and migrant workers and recognise their distinct interests. This article investigates to what extent this shift in attitude informs union responses to cross-border temporary agency work, an important variant of migrant non-standard work in the European Union. This employment form entails several potential lines of intra-labour conflicts of interests, that is, insider versus outsider and domestic versus migrant workers, and thus offers a particularly promising case to study whether and how unions seek to aggregate the interests of an increasingly heterogeneous workforce. Our findings suggest that although trade unions have gained considerable regulatory influence and new capacities to mediate conflicts of interest between different worker groups, a considerable degree of ambiguity remains in union positions and strategies towards temporary agency work and cross-border labour. Instead of gradual steps towards full inclusion of workers regardless of status and origin, union responses are best described as selective representation." (authors' abstract; BIBB-Doku)
Keywords: S 3.5.4.1 Gewerkschaften; P 1.5 Migranten; I 2.2 Europa; Gewerkschaft; Arbeitnehmerinteresse; Selbstverständnis; Ausländischer Arbeitnehmer; Migrant; Europäische Union